The Effect of Stock Prices and Inflation on Stock Returns with Dividend Policy as a Moderating Variable: (Empirical Study of the Consumer Non-Cyclical Sector Listed on the Indonesia Stock Exchange (IDX) for the 2019-2024 Period) - Giovani, Ade (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
This study aims to analyze the influence of Stock Prices and Inflation on Stock Returns by examining the role of Dividend Policy as a moderating variable. This quantitative study utilizes secondary data in the form of audited annual financial reports sourced from the official website of the Indonesia Stock Exchange (IDX). The population of this study was 132 companies in the Consumer Non-Cyclicals sector listed on the IDX between 2019 and 2024. The sampling technique used was purposive sampling, with nine companies meeting the criteria for sample size over six years of observation. The data analysis technique used panel data regression and moderated regression analysis in Eviews 12. The results indicate that Stock Price partially influences Stock Returns. However, when tested as a moderating variable, Dividend Policy was unable to moderate the effect of Stock Price on Stock Returns. Similarly, Dividend Policy was not shown to moderate the effect of Inflation on Stock Returns. These findings suggest that Dividend Policy did not act as an effective adaptation mechanism in the context of the interaction of market and macroeconomic variables in this sector.